VASOVAGAL SYNCOPE: A STUMBLING BLOCK FOR MEDICAL STUDENTS ASPIRING TO BECOME SURGEONS - Saman Khan; Hamna Jabeen Ashraf; Muhammad Ibrahim; Muhammad Osama Riaz; Muhammad Sani; Humna Shah Nawaz; Hassam Ali; Hassan; Muneeba Bashir; Muhammad Ali Taha Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: The objective was to identify the trends of vasovagal syncope in medical students of the Shalamar Medical and Dental College and to determine the association of vasovagal syncope episode with surgical career choice among medical students.Methodology: A quantitative, descriptive cross-sectional study was carried out at Shalamar medical and dental college. Students of clinical years i.e., 3rd, 4th, and final year MBBS were invited to participate in the study.Statistical analysis: Statistical analysis was performed using IBM SPSS 21 for Windows. Data is expressed as mean values, mean ± standard deviation, and frequency trends. The p-value is calculated using the chi- squared test. Two-sided p values